SRC enhanced cisplatin resistance in bladder cancer by reprogramming glycolysis and pentose phosphate pathway - Yuwen Gong; Dongyang Gao; Yibo Shi; Guangrui Fan; Xiaoquan Yu; Enguang Yang; Hui Cheng; Junqiang Tian; Hui Ding; Shanhui Liu; Shengjun Fu; Yan Tao; et al. (Communications Biology)
Abstract The development of cisplatin resistance often results in a grim prognosis in advanced or recurrent bladder cancer. However, effective treatment strategies for cisplatin resistance have not been well established. Herein, we found that overactivation of SRC is associated with cisplatin-resistance. SRC activates hexokinase2 which up-regulates glycolysis and especially the pentose phosphate pathway that leading to increased nucleotide synthesis and NADPH production which can neutralize reactive oxygen species (ROS) induced by cisplatin, thereby protecting bladder cancer cells from cisplatin-induced DNA damage. This phenomenon was effectively reversed by knockout of SRC and inhibition of SRC activity by the SRC inhibitor, eCF506. Moreover, we constructed Cell-derived xenograft (CDX) and Patient-derived xenograft (PDX) from cisplatin-resistant bladder cancer patient. eCF506 exhibited excellent anti-tumor effects and effectively enhanced cisplatin-sensitivity. Altogether, our findings demonstrate that targeting SRC is a promising approach to overcome cisplatin-resistance in bladder cancer, and providing new insights for combination therapy in bladder cancer.